Big data and archaeology : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France) volume 15, session III-1 - Djindjian, François,; Moscati, Paola, (UISPP proceedings series ;, 2021)
The advent of Big Data is a recent and debated issue in Digital Archaeology. Papers consider the historiographic context and current developments, as well as comprehensive examples of a multidisciplinary and integrative approach to the recording, management and exploitation of excavation data and documents produced over a long period of research.